Pertanggung jawaban Hukum Bagi Penyedia Jasa Konstruksi Dan Pengguna Jasa Konstruksi Dalam Kegagalan Bagunan - Daeli, Serta Denius (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Building failure in construction projects can have various legal impacts on construction service providers and users of construction services. This study aims to analyze the form of legal liability that can be imposed on the parties in cases of building failure based on the laws and regulations in force in Indonesia, especially Law Number 2 of 2017 concerning Construction Services. The research method used is normative juridical with a statutory approach and case studies. The results of the study indicate that construction service providers are responsible for building failures that occur due to errors in planning, implementation, or construction supervision. Meanwhile, users of construction services can also be held accountable if they are proven to be negligent in fulfilling their obligations to supervise and maintain buildings. The sanctions that can be imposed are in the form of compensation, administrative sanctions, and even criminal sanctions in certain cases. This study is expected to contribute to the development of construction law in Indonesia and become a reference for construction industry players in understanding the legal aspects related to building failure.